Musical Agency during Physical Exercise Decreases Pain - Fritz, Thomas H.; Bowling, Daniel L.; Contier, Oliver; Grant, Joshua; Schneider, Lydia; Lederer, Annette; Höer, Felicia; Busch, Eric; Villringer, Arno (Frontiers in Psychology, 2018)
Objectives When physical exercise is systematically coupled to music production, exercisers experience improvements in mood, reductions in perceived effort, and enhanced muscular efficiency. The physiology underlying these positive effects remains unknown. One hypothesis suggests that such musical agency stimulates the release of endogenous opioids, which would be highly beneficial for clinical rehabilitation, reducing pain during physical exercise. Design In a cross-over design we tested the opioid-hypothesis with an indirect measure, comparing the pain tolerance of 22 participants following exercise with or without musical agency. Method Physical exercise was coupled to music by integrating weight-training machines with sensors that control music-synthesis in real time. Pain tolerance was measured as withdrawal time in a cold pressor test. Results On average, participants tolerated cold pain for ~5 seconds longer following exercise sessions with musical agency. Musical agency explained 25% of the variance in cold pressor test withdrawal times after factoring out individual differences in general pain sensitivity. Conclusions This result demonstrates a substantial pain reducing effect of musical agency in combination with physical exercise, probably due to stimulation of endogenous opioid mechanisms. This has implications for exercise endurance, both in sports and a multitude of rehabilitative therapies in which physical exercise is effective but painful.